The Relationship between Education Policy and Socioeconomic Inequality - Galena Leila; Jaylin Novia Kimpo (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
The relationship between education policy and socioeconomic inequality in the Philippines is the topic of discussion in this paper. The purpose of the study is to determine whether or not education policy is to blame for socioeconomic inequality in the country by conducting an investigation into the correlation between education policy and socioeconomic standing. According to the findings, there is an inverse relationship between education policy and socioeconomic status. This finding lends credence to the hypothesis that education policy is one of the factors that contribute to socioeconomic inequality. According to the findings of the study, it is vitally important for decision-makers to take into account the potential impact of education policy on socioeconomic inequality when formulating policies. As a strategy for lowering the socioeconomic disparities that exist within the educational system, the research paper suggests giving priority to policies that ensure all students, regardless of their socioeconomic background, have equal access to quality education. The findings of the study have implications for education policy in other countries, particularly those with similar socioeconomic contexts. Additionally, the findings highlight the necessity for policymakers to carefully consider the design and implementation of policies to ensure that they do not contribute to socioeconomic inequality. Additional research is required to identify strategies that are effective in reducing socioeconomic inequality through education policy in the Philippines and in other countries.